Performance analysis of wimax point to multipoint network / Siti Raihan Ahmad - Ahmad, Siti Raihan (2007)
Amidst the rapidly growing deman for high speed internet access in the residential and small office sectors and an equally fast paced growth in last mile access technologies broadband wireless access (BWA) has emerged as a promising solution